Improving Student Well-Being Aspects through Teacher's Instructional Creativity in Islamic Elementary School - Fitria Martanti; Moch Fatkhuronji; Asma’ul Husna; Maskur (Universitas Islam Negeri (UIN) Salatiga, 2023)
Ensuring student well-being has become a pivotal aspect that directly impacts learning outcomes, physical health, and the development of spiritual life. A key avenue for achieving student well-being lies in the ability of both the headmaster to manage the school effectively and the teacher to create a comfortable learning environment. This qualitative research focuses on delineating the efforts undertaken by the Islamic Elementary School of Mangunsari Semarang in realizing student well-being and assessing the creativity of teachers in this pursuit. The research seeks to provide a detailed description based on the real situation at the research site. Data collection techniques involve observation, documentation, and interviews. The findings reveal that the school's efforts in achieving student well-being encompass effective school administration management and the development of understanding, knowledge, values, attitudes, and skills through both intracurricular and co-curricular programs. Furthermore, the school employs special assistance in various fields to ensure student education and support their well-being. The aspects of student well-being are considered comprehensively, encompassing cognitive, emotional, social, spiritual, physical, and personal aspects. Teachers contribute to achieving student well-being through creative approaches , utilizing various media and tailoring learning methods, resources, and materials to suit the students’ needs.